On borrowed land [videorecording] - Westfall, Matthew; Weisman, David ([S.l.] Amphion Production, 1990)
A story of struggle of the squatters to preserve the place they call their home, Reclamation Area in Pasay City.
Narrated by Willem Dafoe; music by Freddie Aguilar, Gary Granada; translators, Cielo Fuentabella, Maria Metcalfe, Miles Raquid, Caroline Jimenez.
Keywords: Squatters -- Philippines; Poor -- Philippines -- Pasay City; Sociology